Impediments for the Uptake of the Botswana Government's Male Circumcision Initiative for HIV Prevention - Motshedisi Sabone; Mabel Magowe; Lesego Busang; Jonathan Moalosi; Benjamin Binagwa; Janet Mwambona (The Scientific World Journal)
Botswana remains one of the countries with high prevalence of HIV infection with a population prevalence rate of 17.6 in 2008. In 2009, the Ministry of Health launched male circumcision as an additional strategy to the already existing HIV preventive efforts. The purpose of this paper is to share what the participants of a survey to evaluate a short-term male circumcision communication strategy in seven health districts of Botswana reported as impediments for the program's uptake. Qualitative data were obtained from 32 key informants and 36 focus group discussions in 2011. Content analysis method was used to analyze data and to derive themes and subthemes. Although male circumcision was generally acceptable to communities in Botswana, the uptake of the program was slow, and participants attributed that to a number of challenges or impediments that were frustrating the initiative. The impediments were organized into sociocultural factors, knowledge/informational factors, and infrastructural and system factors.